EjODO1, a MYB Transcription Factor, Regulating Lignin Biosynthesis in Developing Loquat (Eriobotrya japonica) Fruit - Zhang, Jing; Ge, Hang; Zang, Chen; Li, Xian; Grierson, Donald; Chen, Kun-song; Yin, Xue-ren (Frontiers in Plant Science, 2016)
Lignin is important for plant secondary cell wall formation and participates in resistance to various biotic and abiotic stresses. Loquat undergoes lignification not only in vegetative tissues but also in flesh of postharvest fruit, which adversely affects consumer acceptance. Thus, researches on lignin biosynthesis and regulation are important to understand loquat fruit lignification. In loquat, a gene encoding an enzyme in the lignin biosynthesis pathway, Ej4CL1, was reported to be regulated by transcription factors, including EjMYB1, EjMYB2, EjMYB8 and EjAP2-1, knowledge of this process is still limited. With the aim of identifying novel transcriptional factors controlling lignin biosynthesis in loquat, the promoter of Ej4CL1 was utilized to screen a cDNA library by yeast one hybrid assay. A novel R2R3 MYB, named EjODO1, was identified. Real-time PCR analyses indicated that EjODO1 is highly expressed in lignified stems and roots. During fruit development, expression of EjODO1 decreased along with the reduction of lignin content and became undetectable in mature ripe fruit. Thus, EjODO1 is likely to be involved in lignification of vegetative organs and early fruit development but not in mature fruit or postharvest lignification. Dual-luciferase assay indicated that EjODO1 could trans-activate promoters of lignin biosynthesis genes, such as EjPAL1, Ej4CL1 and Ej4CL5 and transient overexpression of EjODO1 triggered lignin biosynthesis. These results indicate a role for EjODO1 in regulating lignin biosynthesis in loquat which is different from the previously characterized transcription factors.